Anger, revolution, and romanticism - Stauffer, Andrew M (Cambridge University, 2013)
Andrew M. Stauffer explores the changing place of anger in the literature and culture of the Romantic period, particularly in the poetry and prose of Blake, Coleridge, Godwin, Shelley, and Byron. This innovative book has much to contribute to the understanding of Romantic literature and the cultural history of emotions.